An association between electronic nicotine delivery systems use and a history of stroke using the 2016 behavioral risk factor surveillance system. Issue 36 (10th September 2021) - Bricknell, Ryan A.T.; Ducaud, Christobal; Figueroa, Alejandra; Schwarzman, Logan S.; Rodriguez, Pura; Castro, Grettel; Zevallos, Juan Carlos; Barengo, Noël C.
Abstract : Abstract: Electronic nicotine delivery systems (ENDS) are growing in use and many of the health implications with these devices remain unknown. This study aims to assess, using a survey representative of the USA general population, if an association exists between a history of ENDS use and a history of stroke. This cross-sectional study was a secondary data analysis using the 2016 behavioral risk factor surveillance system survey. The main exposure variable of the study was a self-reported history of ENDS use. The main outcome was a self-reported history of stroke. Covariates included sex, race, traditional cigarette use, smokeless tobacco use, chronic kidney disease, diabetes, myocardial infarction, and coronary artery disease. Unadjusted and adjusted logistic regression analyses were done. Adjusted odds ratios (AOR) and their corresponding 95% confidence intervals (CI) were calculated. Of the 486, 303 total behavioral risk factor surveillance system survey participants, 465, 594 met the inclusion criteria for this study of ENDS use and stroke. This study shows that current ENDS use was positively associated with a history of stroke. AOR of some daily ENDS use with stroke was 1.28 (95% CI: 1.02–1.61) and AOR of current daily ENDS use with stroke was 1.62 (95% CI: 1.18–2.31). The majority (55.9%) of current daily ENDS users reported former traditional cigarette smoking. Female sex, non-white ethnicity, elderly age, chronic kidney disease, coronary artery disease, diabetes, and traditional cigarette use characteristics were all also associated with increased odds of reporting a stroke. This study found a statistically significant and positive association between ENDS use and a history of stroke. Further research is warranted to investigate the reproducibility and temporality of this association. Nevertheless, this study contributes to the growing body of knowledge about the potential cardiovascular concerns related to ENDS use and the need for large cohort studies.